Redox-responsive polyprodrug nanoparticles for targeted siRNA delivery and synergistic liver cancer therapy. (March 2020) - Li, Senlin; Saw, Phei Er; Lin, Chunhao; Nie, Yan; Tao, Wei; Farokhzad, Omid C.; Zhang, Lei; Xu, Xiaoding
Abstract: Combination therapy has been developed as an innovative modality for effective cancer therapy. However, the administration of combinatorial therapeutics is limited by the varying pharmacokinetics of different drugs. Although numerous nanoparticles (NPs) can synchronize the delivery of combinatorial therapeutics to tumor cells, their clinical translation is still challenged, which is partly due to the complexity to precisely control the loading of combinatorial therapeutics to maximize therapeutic efficacy and suboptimal NP properties. Herein, a new redox-responsive polyprodrug nanoplatform was developed for targeted siRNA delivery and synergistic cancer therapy. This NP platform is made with redox-responsive 10-hydroxycamptothecin (HCPT)-based polyprodrug (polyHCPT) as the inner core, amphiphilic lipid-poly (ethylene glycol) (lipid-PEG) as the outer shell, and lactobionic acid (LA) decoration on the surface. After siRNA loading and subsequent systemic administration, the resulting NP platform could accumulate in tumor tissues and target hepatoma cells via specific recognition between LA and asialoglycoprotein (ASGP) receptors. With the high concentration of glutathione (GSH) in the cytoplasm to break the disulfide bonds in the polyHCPT, intact HCPT molecules and encapsulated B-cell lymphoma 2 (Bcl-2) siRNA (siBcl-2) could be rapidly released, leading to the synergistic inhibition of tumor growth via the induction of apoptosis by HCPT and the concurrent silencing of the anti-apoptotic gene by siBcl-2. Graphical abstract: Herein we developed a new redox-responsive polyprodrug NP platform for targeted siRNA delivery and synergistic cancer therapy. This long-circulating co-delivery NP platform could respond to the high concentration of GSH in the cytoplasm to induce the fast release of intact HCPT molecules and encapsulated siBcl-2, leading to synergistic inhibition of tumor growth via inducing apoptosis by HCPT and concurrently blocking the anti-apoptotic pathway by siBcl-2. This redox-responsive polyprodrug-based nanoplatform could be used as an effective tool to synchronize the delivery of various combinatorial therapeutics for cancer combination therapy. Image 1